PELABELAN TOTAL VERTEKS IRREGULAR PADA BEBERAPA GRAF HASIL KALI KARTESIUS - RAMDANI , RISMAWATI
A total vertex irregular labeling of a graph G(V (G),E(G)), with v vertices and e edges, is an assignment: f : V (G) ? E(G) ? {1, 2, . . . , r} so that w(v) = f(v) +Pf(uv) are distinct for all vertices v ? V (G). The value of w(v) is called a weight of vertex v. Total vertex irregularity strength of G, denoted by tvs(G), is the minimum r so that G admits a total vertex irregular labeling. In this final project, we consider the total vertex irregular labelings of some cartesian product graphs, namely ladder graphs (P2Pn), book graphs (P2K1,n), pyramidal graphs (C3 Pn) dan graphs C4 Pn.